2016
DOI: 10.1039/c6tb01774f
|View full text |Cite
|
Sign up to set email alerts
|

Diamond-coated ‘black silicon’ as a promising material for high-surface-area electrochemical electrodes and antibacterial surfaces

Abstract: Coating black silicon needles in a uniform layer of conducting boron-doped CVD diamond produces a high-surface-area electrode material that promising for electrochemical applications, as well as acting as a robust bactericidal surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 71 publications
5
75
0
Order By: Relevance
“…The smaller, more-rigid, spherical S. aureus cells have a higher probability of attaching in these non-lethal regions than the larger P. aeruginosa cells. These multi-directional, bimodal nanostructures may exhibit a greater biocidal activity than that of the more regular nanostructures previously investigated, including both naturally occuring 23,25,26,32,[34][35][36][53][54][55] and synthetic 24,27,33,37,48,49,54,57,65 surfaces. This occurs because the bacteria are subjected to forces operating in multiple directions during surface adsorption, which limits their ability to evade critical membrane damage, and hence cell death.…”
Section: Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The smaller, more-rigid, spherical S. aureus cells have a higher probability of attaching in these non-lethal regions than the larger P. aeruginosa cells. These multi-directional, bimodal nanostructures may exhibit a greater biocidal activity than that of the more regular nanostructures previously investigated, including both naturally occuring 23,25,26,32,[34][35][36][53][54][55] and synthetic 24,27,33,37,48,49,54,57,65 surfaces. This occurs because the bacteria are subjected to forces operating in multiple directions during surface adsorption, which limits their ability to evade critical membrane damage, and hence cell death.…”
Section: Concentrationsmentioning
confidence: 99%
“…This effective nanospike height is consistent with that reported in a number of previous studies, 22,23,27,38,46-48 which suggests that a nanofeature height of $300 nm tends to display a greater level of biocidal activity towards both Gram-negative and Gram-positive bacteria than substrata possessing nanospikes with greater or less height. 22,23,27,38,[46][47][48] The reason for the effectiveness of this 'optimal' peak height in killing bacteria is still largely unknown. The inter-pillar spacing on the substrata used in this study was slightly larger than that of a number of previously reported effective antibacterial surfaces, which would initially suggest that nanofeature height plays an important role in the overall bactericidal behaviour of the substrates.…”
Section: 2526mentioning
confidence: 99%
“…May and co‐workers reported a similar approach, but inductively coupled plasma (ICP) etching process of the Si substrate led to the formation of needles (Si Needles) reaching a length of almost 20 μm as shown in Figure A. The diamond coating was obtained by a CVD process when a diborane‐rich CH 4 /H 2 mixture was used, resulting in a heavily boron‐doped micro‐ or nanocrystalline diamond film over the Si needles (Figure B).…”
Section: Cvd‐deposited Diamond Compositesmentioning
confidence: 96%
“…Inspired by nature, a number of studies have since been carried out to develop bactericidal nanotopographies on synthetic materials. They include silicon and diamond coated silicon, titanium and its alloy, polymers, stainless steel, and aluminium . Table 3 lists a summary of biomimetic bactericidal surfaces on various materials currently in development.…”
Section: Antimicrobial Nanotopographiesmentioning
confidence: 99%